The Application of Value at Risk in Chinese Commercial Banks for the Foreign Exchange Rate Risk Management - Bao, Xiuli (2009)
This paper mainly discusses the application of VaR models in the commercial banks of China for the foreign exchange rate risk management, comparing three basic approach of VaR: variance-covariance method, historical simulation approach and Monte Carlo approach.